A Study Of Main Characters Conflict In 1917 Movie - Gultom, Nursalma (Jurnal Ilmiah Mahasiswa Pendidikan [JIMEDU], 2021)
This research was aimed to find out the main character conflict in the "1917" movie by analyzing the evidence from the dialogues and his actions in the film. And to know what the conflict in the main character of Schofield. Qualitative method was used in this research. The reseacheremployedherself to collect the data by reading script, watching the film and marking them. The reseacherused the "1917" movie by Sam Mandes released in 2019. In this analysis, the reseacherfound out about the conflict of Schofield as main character. Schofield faced two conflicts, namely Internal conflicts and external conflicts. Schofield is young soldier from England tasked with delivering a message to prevent more soldiers from falling. From the research conducted, the researcher found the conflict experienced by Schofield, there were 4 data in Internal conflict and 6 data for external conflict, there is only 1 type of external conflict found,The result of this research was expected to give some contributions to further study of conflict. Based on the result above, It was hoped that the readers can develop and increase knowledge about all the aspect of conflict and the types of conflict in the movie.The researcher hope the result of the research will give additional information, contributions and stimulates the students or readers in studying the literature.